Putusan Permanen Court Of Arbitration Dalam Sengketa Antara Philipina-China Dan Implikasinya Bagi Stabilitas Keamanan Di Laut China Selatan - Yavier Pattiasina; Josina Augustina Yvonne Wattimena; Johanis Steny Franco Peilouw (Faculty of Law, Universitas Pattimura, 2022)
Introduction: The Permanent Court of Arbitration (PCA) clarifies China's claim regarding historic rights in relation to maritime areas in the South China Sea which are claimed using the nine-dash line, which is contrary to the 1982 Law of the Sea Convention because in 2016 it was contrary to the 1982 Law of the Sea Convention because in 2016 the Permanent Court of Arbitration (PCA) has declared that the area(Reed Bank) is within the Philippine Exclusive Economic Zone.Purposes of the Research: This writing aims to understand and determine the nature of the decision of the permanent court of arbitration in the dispute between the Philippines-China in the South China Sea. Methods of the Research: The research method in this paper uses a prescriptive analytical research type. The research approach used is a statutory approach, a conceptual approach and a case approach. The procedure for collecting legal materials uses primary legal materials and secondary legal materials through books, articles, journals and the writings of legal experts, as well as legal materials analysis techniques in this study using qualitative analysis techniques.Results of the Research: The result obtained is that the decision of the Permanent Court of Arbitration (PCA) is final and binding, meaning it must be respected and obeyed by the parties to the dispute, therefore China's argument regarding the nine dash line is an international violation because it does not respect the Permanent Court of Arbitration (PCA) as a the institution that handles the dispute has issued a decision. The implication of the decision of the Permanent Court of Arbitration (PCA) for security stability in the South China Sea is that the PCA decision related to the SCS dispute is a clarification or interpretation of the PCA against the 1982 Law of the Sea Convention so that it can become a source of law that is generally accepted or binding on all countries. The PCA decision can be used as a means to weaken China's argument.